Anodic Cyclization of Dimethyl 2-(3-Oxo-3-arylpropyl) Malonates into the Corresponding Dimethyl 2-Aroylcyclopropane-1,1-dicarboxylates - Okimoto, Mitsuhiro; Yamamori, Haruki; Ohashi, Kousuke; Hoshi, Masayuki; Yoshida, Takashi (Synlett, 2013)
A variety of dimethyl 2-(3-oxo-3-arylpropyl)malonates were electrooxidized in methanol, in the presence of potassium iodide and a base or a neutral salt, to give the corresponding cyclized dimethyl 2-aroylcyclopropane-1,1-dicarboxylates in moderate to good yields. The reactions were carried out under extremely mild reaction conditions, in which the optimal amount of electrolytic current varied from 2.12–2.41 F·mol–1 depending on the substrates. The reaction presumably proceeds via a two-electron oxidation process, in which iodide ions play an important role as the electron carrier between the anode and the substrate.
Keywords: oxidation; electron transfer; radicals; cyclization; substituent effects; ring closure; green chemistry; iodine